Lokus Kecerdasan Spiritual dalam Perspektif Al-Qur’an Kajian Tematik atas Peran Sentra Qalbu - Iskandar, Iskandar (SUHUF, 2012)
One of the most precious aspects of all human potential is intelligence. Intel-ligence, which arises from the human brain, has been able to bring people to advanced stages of civilization. However, these advancements cannot always be enjoyed by modern society as there are those who continue to experience alienation and isolation. This fact has encouraged the emergence of a concept of intelligence which is based on spiritual, and not merely intellectual strength. It is popularly called ‘the spiritual intelligence’. This article utilises a thematic interpretative approach to explain how the Qur'an views the concept of intelligence as poessessed by individuals.